Effects of Beta Vinasse Supplementation on Performance, Meat Quality and Ilio- Caecal Microflora in Quail Rations - Yeşilbağ, DY; Cetin, I; Cengiz, SS; Cetin, E; Sarpasar, M (Journal of the Hellenic Veterinary Medical Society, 2023)
The aim of this study was to evaluate the effects of β-vinasse supplementation on the live weight (LW), live weight gain (LWG), feed intake (FI), feed conversion ratio (FCR), carcass yield, meat quality and ilio-caecal bacteriological flora of quails. A total of 240 5-d-old Japanese (Coturnix coturnix Japonica) quails, including both males and females, were divided into 3 groups 80 quails and treated as follow: a control group with 0 g β-vinasse/kg ration; (2) 15 g/kg β-vinasse and (3) 30 g/kg β-vinasse. The study lasted for 6 weeks. At the end of the experiment, suplementation with β-vinasse did not have significant effect on FI and FCR. Dietary supplementation with 30 g/kg β-vinasse significantly (P < 0.05) increased LW (21 d) and LWG (5 to 21 d). The dietary treatment of quails with different levels of β- vinasse did not effect on hot carcass weight, cold carcass weights, hot and cold carcass yields and breast and thigh pH. The lightness (L*) and yellowness (b*) of breast values were significantly (P<0.05) increased of 30 g/kg supplementation. Different levels of β-vinasse significantly increased Lactobacillus spp. in faeces. As a result, it was concluded that β-vinasse (by-product obtained from molasses) can be used in quail diets as an alternative feed source that will meet the nutritional needs of the animal and have positive effects on the digestive system, especially on the intestinal health ( an increase in Lactobacillus spp. counts).